KISAH SUKSES TIM PEMANTAU JENTIK RUTIN RT DALAM MENINGKATKAN ABJ DI KELURAHAN KRAMAS - Arina Azmy Trisetyo Utami; Priyadi Nugraha Prabamukti; Besar Tirto Husodo (Jurnal Kesehatan Masyarakat (Undip), 2018)
Dengue Hemorrhagic Fever (DHF) is a dangerous infectious disease caused by dengue virus infection and transmitted through the bite of Aedes aegypti and Aedes albopictus mosquitoes. In Semarang, the CFR of DHF entered the national high category for six years in a row. Efforts to control dengue fever are carried out through vector control, which is emphasized on community empowerment, namely the establishment of the Routine larvae team. The study aimed to analyze the factors related to the success of the routine larvae monitoring team in neighborhood to increase larvae-free rates  in the Kramas Village Semarang. This research is an observational study using cross sectional study. The population of this research is the active RTR RT team in Kramas Village. The sampling technique is total sampling totaling 65 people. The results showed that the support of RT leaders (p-value = 0.011) and community support (p-value = 0.008) were related to the practices of PJR RT teams that supported the success of increasing ABJ in Kramas Village. For the respondent's age, last education, occupation, length of time to become an PJR RT team, knowledge, attitudes, village regulations, availability of facilities, support of health workers, support from vilage officers, family support and peer support were not related to the success of the routine larvae monitoring team in neighborhood to increase larvae-free rates  in the Kramas Village Semarang. The assistance of the head of the neighborhood and the community can optimize both support in an effort to the success of the  routine larvae monitoring team in neighborhood to increase the number of larva free in its area.